REMEDIASI MISKONSEPSI GERAK LURUS BERATURAN MENGGUNAKAN MODEL THINK PAIR SHARE UNTUK PESERTA DIDIK SMP - Oktafia, Reni; Sitompul, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine the effectiveness of Think Pair Share (TPS) learning models to reducing students' misconceptions about straight-line motion with constant velocity (GLB) in grade 7th of SMP Negeri 3 Sungai Raya. This research used pre-experiment design method with one group pre-test post-test design. Intact group was used as sampling technique with number of sample is 28 students. Data collected using measurement technique by collecting the results of pre-test and post-test. The research found that students experienced misconceptions on all indicators. There was a significant change in the number of misconceptions before and after remediation using the TPS learning model (Wilcoxon Test analysis results). There was a significant change in the indicators of identification of GLB characteristics, while there is no significant change in the indicators of differences in distance and displacement in one-dimensional motion and two-dimensional motion, differences in speed and velocity, definition of GLB, and determining the v-t graph in GLB (Mc Nemar Test analysis results). Remediation using TPS learning model effective to reducing students' misconceptions about GLB (ES = 1.41). This research expected to be used as reference for further research, especially alternatives in the selection of learning models.Keywords: Misconception, Remediation, Straight-Line Motion with Constant Velocity                 (GLB), Think Pair Share.